Effect of Cooking Techniques on the in vitro Protein Digestibility, Fatty Acid Profile, and Oxidative Status of Mealworms (Tenebrio molitor) - Mancini, Simone; Mattioli, Simona; Paolucci, Simone; Fratini, Filippo; Dal Bosco, Alessandro; Tuccinardi, Tiziano; Paci, Gisella (Frontiers in Veterinary Science, 2021)
Tenebrio molitor (mealworm) larvae are one of the most promising insects for feed-food purposes. Mealworms are rich in several macro and micro nutritional elements and can be practically reared on side stream substrates. In this study the effects of seven different cooking techniques were tested on the nutritional value of mealworms focusing the attention on the protein digestibility, the fatty acid profile and the oxidative status. Uncooked larvae (UC) were used as control and compared to two combinations temperature/time in oven cooking (70 °C for 30 minutes, OC70-30, 150 °C for 10 minutes, OC150-10), two methods of frying (mealworms fried in sunflower oil as deep fry, DF, or pan fry, PF), microwaving (MW), boiling (in plastic bag under vacuum, BO) and steaming (ST). Proximate composition, in vitro digestibility (gastric and duodenal), fatty acids (FA) profile and oxidative status (tocopherol and tocotrienol, carbonyl and lipid oxidation) were then tested. Cooking technique affected all the tested parameters. As expected, cooking affected proximate composition in relation to the method applied (dry matter increased after oven cooking and frying; lipids increased by frying). In vitro digestion revealed highest value for OC70-30 method, followed by UC, ST. Deep frying revealed the worst digestibility percentage. Fatty acids profile was deeply affected by the cooking technique, with general decrease in SFA and MUFA. The highest modifications in FA profile were revealed in ST larvae with and increased percentage of linoleic acid linked to the lowering of SFA and MUFA contents. Furthermore, deep frying larvae in sunflower oil increased the relative abundance of PUFAs. Tocols values were higher in DF and MW groups than PF (about 6-fold more) and all other groups (7-fold more). Carbonyls increased with oven cooking (OC150-10 and OC70-30), whereas the values were lower with frying and similar to ST and UC. Lipid oxidation was highest as well in OC150-10 but similar to frying methods (DF and PF). Basing on the obtained results it can be concluded that surely mealworm larvae meet human nutritional requirements but cooking method must be carefully chosen to maintain a high nutritional value.